1994
DOI: 10.1177/0146167294204009
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Coping with Stress: When Stressor and Appraisals Do Not Differ

Abstract: In an attempt to control for the effects of event type on sex differences in coping, men and women responded to an identical achievement-related stressor under controlled laboratory conditions. Although men and women were similar in their cognitive appraisal of the situation, they nonetheless reported differences in preparatory coping. Women reported seeking social support and using emotion-focused coping to a greater extent than men, whereas men reported using relatively more problem-focused coping than women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

36
241
5
18

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(313 citation statements)
references
References 44 publications
36
241
5
18
Order By: Relevance
“…Lazarus and Folkman [19] suggest that sometimes the use of emotion-focused coping prevents the individual from searching for solutions to a solvable problem, and therefore becomes a counterproductive strategy. Emotion-focused coping styles have been associated with poorer outcome in the general stress and coping literature [41] as well as in the patient literature [20,42], and specifically when examining husbands of patients [43,44]. In our sample, problem-focused coping only correlated mildly with social support and education, but not with role strains or mood, as was expected.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Lazarus and Folkman [19] suggest that sometimes the use of emotion-focused coping prevents the individual from searching for solutions to a solvable problem, and therefore becomes a counterproductive strategy. Emotion-focused coping styles have been associated with poorer outcome in the general stress and coping literature [41] as well as in the patient literature [20,42], and specifically when examining husbands of patients [43,44]. In our sample, problem-focused coping only correlated mildly with social support and education, but not with role strains or mood, as was expected.…”
Section: Discussionsupporting
confidence: 69%
“…The relation between problem-focused coping and the various measures of burden was practically nonexistent when examined through correlation analyses, although the relation between mood and this type of coping was similar to that of mood and emotion-focused coping. There is a large body of research that supports the relation between use of more problem-focused coping and better mood [44]. However, the fact that burden did not relate to problem-focused coping was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars suggested that women find themselves in stressful circumstances more often than men (e.g., Almeida & Kessler, 1998;McDonough & Walters, 2001). Other researchers have suggested that it is possible that women assess threatening events as more stressful than men do (Ptacek, Smith, & Dodge, 1994). Klonoff, Landrine, and Campbell (2000) suggested that women experience gender-specific stressors such as gender violence and sexist discrimination, which are associated with women's physical and psychiatric events.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Matud (2004) found that women reported more stress than men when taking into account the effects of stress exposure, the enduring nature of some role-related stressors, and other long-term chronic and daily stressors. Furthermore, research has shown that men make more frequent use of instrumental coping, while women are more likely to use emotion-focused coping (Ptacek, Smith, & Dodge, 1994). However, studies indicated that long-term stressors may reduce physical or social resources for coping with new stressors, thus making individuals more vulnerable to the harmful health effects of severe stressors (Grzywacz, Almeida, Neupert, & Ettner, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…El dolor crónico afecta más a las mujeres que a los hombres (9), planteándose que las mujeres utilizan más estrategias centradas en la emoción y los hombres más las centradas en el problema (10); pero también se afirma que utilizan más estrategias adaptativas por considerar que ejercen mayor control sobre la enfermedad (11), lo cual entraría en contradicción con el modelo básico de Lazarus y Folkman (1984), en donde se establece que la menor percepción de control se relaciona con una valoración secundaria menor (menos opciones de actuación) y mayor uso de estrategias centradas en la emoción. También hay trabajos que afirman que los hombres utilizan ante el dolor más estrategias centradas en la emoción que las mujeres (12), aunque hay estudios que indican lo contrario, observando que las mujeres utilizan más la distracción, reevaluación positiva o la religión (13), estrategias que se encuentran entre las centradas en la emoción.…”
unclassified